Safety profile of biologic therapy in Polish paediatric patients with Crohn’s disease - Szymanska, Edyta; Dadalski, Maciej; Oracz, Grzegorz; Kierkus, Jarosław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : In recent years, monoclonal antibodies against tumor necrosis factor α (TNF-α), infliximab (IFX), and adalimumab (ADA) have gained increasing popularity in Crohn’s disease (CD) management. Many clinical trials have shown that biologics are a generally well-tolerated and safe treatment. However, the follow-up time with regards to safety is too short, and data on that issue are still limited. Aim : To report the cumulative safety profile of biologic therapy with IFX and/or ADA, up to 8 years, in Polish children with moderately to severely active CD. Material and methods : We performed a retrospective analysis of 110 children, aged 13.0 ±9.3 years, diagnosed with CD, and treated with IFX and/or ADA, within a period of 8 years between 2005 and 2013. Safety data for all treated patients were collected throughout the entire treatment period and were included in the safety analyses. Results: The cumulative rates of treatment-related adverse events (AE) (TRAEs) in all patients were 67 events – 43 (64.17%) events for IFX and 24 (35.83%) for ADA, respectively. The majority of TEAEs were mild-to-moderate in intensity. The most frequently reported ones were: anaemia in 17 (20.23%) IFX patients and 9 (23.08%) ADA patients, and mild infections in 9 (10.7%) IFX patients and 5 (12.8%) ADA patients, respectively. We did not report any serious AE (sAE). Conclusions : Biologic therapy with infliximab and/or adalimumab is generally well tolerated and safe, and does not cause any sAEs.